Knowledge, Attitudes, and Determinants of Beyond-Use Date (BUD) Drug Management in the Community - Aprilia Syafaria; Evi Mustiqawati; Restu Harisma Damayanti (Journal of Health Science and Pharmacy, 2026)
Background: The obligation to include the Beyond Use Date (BUD) on medication containers constitutes an essential component of pharmaceutical management aimed at ensuring the safe, rational, and effective use of medicines. BUD refers to the time limit for the use of a drug product after compounding, preparation, or after the primary packaging has been opened or compromised. The absence of proper BUD labeling may increase the risk of medication misuse, as drugs used beyond their BUD may experience reduced stability, degradation of active substances, and potential negative health effects. Despite its importance, the implementation of BUD labeling on medication packaging in Indonesia remains limited. Objectives: This study aimed to determine the level of knowledge, attitudes, and associated factors related to Beyond Use Date (BUD) management of medicines among the community at Waborobo Public Health Center, Betoambari Subdistrict, Baubau City. Methods: This study employed a descriptive non-experimental design. The sampling technique used was purposive sampling, involving 88 respondents who sought outpatient treatment at Waborobo Public Health Center between May and June 2024. Primary data were collected using a structured questionnaire. Data were analyzed using descriptive statistical methods and the Chi-square test to examine associations between variables. Results: The results showed that, among 88 respondents, the majority demonstrated a fairly good level of knowledge regarding drug BUD management (74.14%). Additionally, 74.37% of respondents exhibited positive attitudes toward BUD management. Chi-square analysis revealed a significant association between knowledge of BUD management and educational background (p = 0.000; C = 0.527), as well as between knowledge and attitude (p = 0.000; C = 0.501). A significant relationship was also identified between educational background and attitudes toward BUD management (p = 0.025; C = 0.408). Conclusion: The community at Waborobo Public Health Center generally demonstrated fairly good knowledge and positive attitudes regarding Beyond Use Date (BUD) management of medicines. Educational background was significantly associated with knowledge and attitudes, indicating that education plays an important role in improving public awareness and appropriate medication management practices. Strengthening educational interventions may enhance proper BUD implementation in the community. Keywords: Beyond Use Date; medication management; community knowledge; attitudes; public health